Copper deficiency, a rare but correctable cause of pancytopenia: a review of literature. Issue 11 (2nd November 2022) - Tahir, Nayha; Ashraf, Aqsa; Waqar, Syed Hamza Bin; Rafae, Abdul; Kantamneni, Leela; Sheikh, Taha; Khan, Rafiullah
ABSTRACT: Introduction: Copper is increasingly being recognized as a vital mineral required by both animals and humans. It plays a vital role in many metabolic processes such as cellular respiration, iron oxidation, and hemoglobin synthesis. Copper deficiency, which can be hereditary or acquired, can lead to a wide spectrum of disease processes such as ringed sideroblastic anemia, myelodysplasia, and pancytopenia. Timely identification and management of copper deficiency is necessary to prevent irreversible complications. Areas Covered: Our study focuses on prevalence, etiology, pathophysiology, complications, and treatment of copper deficiency. Expert Opinion: Copper deficiency is frequently underrecognized as the cause of anemia, neutropenia, and bone marrow dysplasia. As it is potentially treatable, it should always be kept in the differentials when patients present with neurological and hematological abnormalities.